Formative evaluation of M.S. Epidemiology (Clinical Epidemiology) - Tan-Torres, Tessa L. (1995)
A formative evaluation of the M.S. Epidemiology (clinical epidemiology) program was carried out on its fourth year of operation. The evaluation was intended to detect the strengths and weaknesses of the program and reinforce and correct these respectively. Because the program had been admitting at least 10 students every year since it started, it was felt that there was enough experience with the program and that any ?growing? pains initially present have been outgrown. It was also felt that an early evaluation, even earlier than that stipulated by the university at five years, would allow more students to benefit from any changes to be instituted. The formative evaluation was based on Stufflebeam's CIPP model: Context, Input, Process, Product. The context evaluation examined whether the needs of the situation were met by the stated objectives of the program. The input evaluation determined how successful the program was implemented. Finally, a preliminary product evaluation assessed whether the graduates of the program are working to reduce the previously stated needs of the situation. This evaluation, being formative, centered more on input and process with a retroactive context evaluation. The main sources of information for the evaluation were the students through their feedback forms and the records of focus group meetings held regularly at the end of the quarter/semester. Another major source of information was the site visit reports of external experts who came yearly. A survey of the faculty was carried out to describe their teaching attitudes and practices and to diagnose their learning needs with regard to pedagogy. Finally, an extensive document review was undertaken. In general, the M.S. Epidemiology program was judged as having the needed resources and being implemented in a process consistent with its objectives. The judgment is based on both the standards of content experts (the site visitors and the evaluator) and the feedback of the consumers-students. The major findings are: 1) the identified need was for clinicians to become better practitioners and to contribute to the health status of the community. The proposed solution was for the clinician to practice evidence-based medicine and to acquire a ?population perspective? through training in clinical epidemiology. In the form approved by the university after taking into account existing courses and internal fiscal constraints, the M.S. Epidemiology does not directly correspond to the proposed solution. The clinician is currently learning numerous tools of epidemiology, more than those needed in clinical practice, and enough to qualify him as an epidemiologist.
Major project (Master of Health Professions Education)--University of the Philippines Manila
Keywords: Clinical epidemiology